Effect of solvent/disinfectant ethanol on the micro-surface structure and properties of multiphase denture base polymers - Basauarajappa S; Al-Kheraif AAA; ElSharawy M; Vallittu PK (ELSEVIER SCIENCE BV, 2025)
Conclusion: The present study demonstrated that denture base polymers, especially autopolymerized denture base polymer is prone for surface crazing and dissolving by solvent/disinfectant ethanol. The interphase region between the PMMA polymer bead and the polymer matrix was most affected by the ethanol. (C) 2015 Elsevier Ltd. All rights reserved.